US Ethnic Group Differences in Family Member Support for People With Diabetes in the 2nd Diabetes Attitudes, Wishes and Needs (DAWN2) Study. Issue 3 (June 2018) - Peyrot, Mark; Egede, Leonard; Funnell, Martha; Hsu, William; Ruggiero, Laurie; Stuckey, Heather
Purpose: The purpose of the study was to describe the perceptions of family members (FM) and people with diabetes (PWD) regarding the frequency and helpfulness of FM support for PWD, including differences among US ethnic groups. Methods: The US 2nd Diabetes Attitudes, Wishes and Needs (DAWN2) substudy was a survey of independent samples of 238 adult FM and 540 adult PWD. Outcome measures included ratings by FM and PWD of the frequency and perceived helpfulness of 7 FM support behaviors and composite scores for frequency and helpfulness. Results: Ratings of individual FM support behaviors were strongly correlated between FM and PWD but significantly different among behaviors. FM and PWD reported most frequent support for listening, assisting, and doing activities with PWD and reporting PWD was doing poorly least frequently. Both groups reported listening, assisting, and reporting PWD was doing well as most helpful; reporting PWD was doing poorly was least helpful. PWD rated support and helpfulness of most behaviors lower than FM. Composite measures of support frequency and helpfulness were strongly correlated for both FM and PWD. Ethnic minority PWD and FM reported most support behaviors as more frequent and more helpful than non-Hispanic white Americans. Conclusions: FM more frequently engage in the support behaviors they view as most helpful, but PWD perceive support to be less frequent and less helpful than FM. FM support differs across ethnic groups, with ethnic minorities reporting higher support frequency and helpfulness. Diabetes care providers should consider ethnic group differences in FM support for PWD.